2013
DOI: 10.1074/jbc.m113.492876
|View full text |Cite
|
Sign up to set email alerts
|

Gel-based Protease Proteomics for Identifying the Novel Calpain Substrates in Dopaminergic Neuronal Cell

Abstract: Background:It is important to assess contribution of calpain activation and identify substrates affected during neurodegeneration. Results: Gel-based protease proteomics identified novel substrates that were cleaved in neurotoxin-treated culture and rat brain disease models. Conclusion: These novel calpain substrates may confer protection against neurodegeneration. Significance: Our findings contribute to better deciphering the molecular mechanism underlying the progression of proteasemediated neurodegeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…30 In accordance with the results of pharmacological inhibition of calpain, MN9D cells overexpressing calbindin-D-28K showed preservation of cdr2, resulting in more resistance to MPP + -induced cytotoxicity. Similarly, we demonstrated that MN9D cells overexpressing cdr2 are less vulnerable to MPP + -induced cytotoxic damage.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…30 In accordance with the results of pharmacological inhibition of calpain, MN9D cells overexpressing calbindin-D-28K showed preservation of cdr2, resulting in more resistance to MPP + -induced cytotoxicity. Similarly, we demonstrated that MN9D cells overexpressing cdr2 are less vulnerable to MPP + -induced cytotoxic damage.…”
Section: Discussionsupporting
confidence: 75%
“…Consequently, pharmacological inhibition of these enzymes successfully blocked MPP + -induced degradation of cdr2 and subsequent dopaminergic neurodegeneration. Previous studies, including ones from our laboratory, report that MPP + -induced calpain activation via increased intracellular Ca 2+ leads to cleavage of numerous cellular substrates and contributes to neuronal cell death, 28, 30, 43, 44 supporting the notion that degradation of critical cellular proteins by activated calpain may be linked to dopaminergic neurodegeneration. An increase in intracellular free Ca 2+ is also known to occur in acute neurodegenerative conditions such as ischemic stroke and spinal cord injury.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…These post-translational modifications are exponential due to a multitude of environmental effects spanning different individuals [6]. Magnitudes of proteomes span over 8-10 orders, whereas current mass spectrometer can only analyze up to 4 orders, add a challenge to this study [7].…”
Section: Introductionmentioning
confidence: 99%